2015
DOI: 10.1371/journal.pone.0116515
|View full text |Cite|
|
Sign up to set email alerts
|

The Acetate/ACSS2 Switch Regulates HIF-2 Stress Signaling in the Tumor Cell Microenvironment

Abstract: Optimal stress signaling by Hypoxia Inducible Factor 2 (HIF-2) during low oxygen states or hypoxia requires coupled actions of a specific coactivator/lysine acetyltransferase, Creb binding protein (CBP), and a specific deacetylase, Sirtuin 1 (SIRT1). We recently reported that acetylation of HIF-2 by CBP also requires a specific acetyl CoA generator, acetate-dependent acetyl CoA synthetase 2 (ACSS2). In this study, we demonstrate that ACSS2/HIF-2 signaling is active not only during hypoxia, but also during gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
94
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(98 citation statements)
references
References 36 publications
3
94
1
Order By: Relevance
“…Through such a mechanism, acetylation of specific proteins may be regulated not only by the relevant acetyltransferase, but also by a specific acetyl-CoA producing enzyme. Consistent with this possibility, acetylation of HIF2α was shown to be exclusively dependent on ACSS2 as a source of acetyl-CoA (Chen et al, 2015; Xu et al, 2014). A third possibility is that ACLY-deficient conditions may result in altered KAT or HDAC activity.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Through such a mechanism, acetylation of specific proteins may be regulated not only by the relevant acetyltransferase, but also by a specific acetyl-CoA producing enzyme. Consistent with this possibility, acetylation of HIF2α was shown to be exclusively dependent on ACSS2 as a source of acetyl-CoA (Chen et al, 2015; Xu et al, 2014). A third possibility is that ACLY-deficient conditions may result in altered KAT or HDAC activity.…”
Section: Discussionmentioning
confidence: 58%
“…First, it may be that in MEFs, an insufficient amount of ACSS2 is present in the nucleus to efficiently drive histone acetylation. ACSS2 has been found to localize prominently to the nucleus in some conditions (Chen et al, 2015; Comerford et al, 2014; Xu et al, 2014), and thus investigation of whether acetate more readily contributes to overall histone acetylation levels in these contexts will be informative. However, potentially arguing against this possibility, hypoxia promotes ACSS2 nuclear localization (Xu et al, 2014); yet, while acetate does regulate histone acetylation in hypoxic cells, a high level of acetate (~2.5 mM) is required (Gao et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, HIF-2α transactivation is reported as being sensitive to the composition of cell culture media. HIF-2α specifically acts as a response factor to glucose concentration in media 47,48 . Media supplemented with acetate, which can be released by tumors, results in acetylation of HIF-2α and nuclear localization of an acetate-dependent acetyl CoA synthetase ACSS2 required for induction 49 .…”
Section: Discussionmentioning
confidence: 99%
“…They also showed that HIF-2α acetylation under hypoxia is reversed, i.e., deacetylated, by Sirtuin 1 (Sirt1) and that the deacetylation process augments rather than dampens HIF-2 signaling [53]. Although the precise mechanism is yet to be determined, this cyclical acetylation by CBP and deacetylation by Sirt1 appears to be necessary for efficient HIF-2 signaling during hypoxia rather than being only an on/off switch [52,54].…”
Section: Noncanonical Hif Regulation In the Kidneymentioning
confidence: 99%